Downregulation of Rab25 activates Akt1 in head and neck squamous cell carcinoma - SEVEN, DIDEM (Oncol Lett, 2015)
Several studies have suggested that Ras-associated binding 25 protein (Rab25) is involved in the pathogenesis of human cancer. Although it has been demonstrated that the development of head and neck squamous cell carcinoma (HNSCC) is the result of an accumulation of multiple sequential genetic and epigenetic alterations in key genes with important functions in cell growth and the cell cycle, recent studies have indicated that HNSCC is a complex and heterogenous disease. To the best of our knowledge, there is no data regarding the regulation of the Rab25 gene at the mRNA or protein level in HNSCC. Furthermore, available data on Rab25 expression in other types of cancer are conflicting. The aim of the present study was to investigate whether Rab25 is involved in the development and/or progression of HNSCC, and to analyze the mechanisms underlying its effects in this type of cancer. The expression of Rab25 mRNA in HNSCC tissues and adjacent non-tumor tissue samples was measured using reverse transcription-quantitative polymerase chain reaction, while the level of the Rab25, Akt1 and phosphorylated-Akt1 proteins was measured using western blotting. Expression of Rab25 mRNA and protein was downregulated in 69.1% and 56.1% of tumor tissue samples, respectively. This downregulation was associated with an increase in p-Akt1 expression, in the absence of a change in total Akt1 protein levels, in tumor tissues compared with normal tissues. The current findings suggest that Rab25 acts as a tumor suppressor in HNSCC.